Recent RhIG Administration Does Not Interfere with the Rosette Test. (9th November 2022) - Zheng, L; Tormey, C; Guarente, J
Abstract: Introduction/Objective: Administration of Rh immune globulin (RhIG) is indicated mid-gestation (28 weeks) and after delivery to prevent Rh D sensitization in Rh D negative women. Women with sporadic prenatal care may not receive the first dose at 28 weeks, and may end up receiving their first dose closer to delivery. The rosette test (RT) is a rapid screen for fetomaternal hemorrhage (FMH) that uses an IgM anti-D antibody to detect fetal Rh D positive red blood cells (RBC) in maternal circulation. It is not currently known if or how recent administration of RhIG prior to performance of a RT may interfere with RBC agglutination and test results. Methods/Case Report: To approximate mixing of fetal Rh D positive RBC with maternal Rh D negative RBC during FMH, 2% volume of Rh D positive RBC from fetal cord and adult donor samples were spiked into Rh D negative RBC. These mixtures were then incubated with a physiologic concentration of RhIG to occupy all Rh D antigen sites on the Rh D positive cells prior to performing the RT. Results (if a Case Study enter NA): Addition of Rh D positive RBC and RhIG to Rh D negative RBC did not affect rosette formation. Rh D negative cells had 0 rosettes/LPF. Rh D negative cells spiked with 2% Rh D positive adult donor and fetal cord RBC by volume produced an average of 9.8 rosettes/LPF (SD: 2.8) and 11.2 (SD: 3.3), respectively. Addition of a physiologic concentration of RhIG to the spiked Rh D positive adult donor and fetal cord RBC produced an average of 13.0 rosettes/LPF (SD: 2.5) and 11.2 rosettes/LPF (SD: 2.6), respectively. Conclusion: Incubation of Rh D positive RBCs with physiologic concentration of RhIG does not affect the rosette test. Clinicians and laboratorians should be reassured that the rosette test continues to be an accurate way to quantitate FMH after recent RhIG administration.